Answer:
dont understand clearly
Step-by-step explanation:
dont understand clearly
Answer:
The required equation is 5x - 3 = 12
Step-by-step explanation:
We have to find the equation for the given condition
Let the number be x as given in the equation
Now according to the condition
5 time the Number is 5 *x = 5x
Three less then 5 time the Number would be 5x - 3
And all of it is equal to 12
Which gives us the equation
5x - 3 =12
The required equation is <em>5x - 3 = 12</em>
Answer:
Check the explanation
Step-by-step explanation:
Part A: the sum of Side 1 and Side 2= 5x^2+7x-4
Part B all you have to do is the same thing, but subtract the sum of side 1 and 2 from the total. 5x^3-0x^3=? 4x^2-5x^2=? -x-7x=? -3-4=?
Part C:The closure property states that one polynomial plus another polynomial is also a polynomial. It is the same for addition, subtraction, multiplication, and division